1999
DOI: 10.1016/s1097-2765(00)80187-2
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Eukaryotic Protein Phosphatase Required for Transcription by RNA Polymerase II and CTD Dephosphorylation in S. cerevisiae

Abstract: The carboxy-terminal domain (CTD) of the largest subunit of RNA polymerase II is phosphorylated soon after transcriptional initiation. We show here that the essential FCP1 gene of S. cerevisiae is linked genetically to RNA polymerase II and encodes a CTD phosphatase essential for dephosphorylation of RNA polymerase II in vivo. Fcp1p contains a phosphatase motif, psi psi psi DXDX(T/V)psi psi, which is novel for eukaryotic protein phosphatases and essential for Fcp1p to function in vivo. This motif is also requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
225
1
2

Year Published

2000
2000
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(239 citation statements)
references
References 30 publications
(3 reference statements)
10
225
1
2
Order By: Relevance
“…The phosphatase Fcp1p dephosphorylates the C-terminal domain (CTD) of Pol II and is generally required for Pol II transcription in yeast (31,32). It was reported that fcp1-ts mutants had defects in Pol I transcription, and Fcp1p stimulated transcription by Pol I in vitro in specific and nonspecific transcription assays, supporting a role for Fcp1p in Pol I elongation (33).…”
Section: Discussionmentioning
confidence: 99%
“…The phosphatase Fcp1p dephosphorylates the C-terminal domain (CTD) of Pol II and is generally required for Pol II transcription in yeast (31,32). It was reported that fcp1-ts mutants had defects in Pol I transcription, and Fcp1p stimulated transcription by Pol I in vitro in specific and nonspecific transcription assays, supporting a role for Fcp1p in Pol I elongation (33).…”
Section: Discussionmentioning
confidence: 99%
“…does not display any homology with other known protein phosphatases but possesses an unusual catalytic site present in a subset of phosphotransferases (13,14). FCP1 is a highly specific phosphatase as the CTD within a functional RNAP II remains its only known protein substrate.…”
Section: Rna Polymerase II (Rnap Ii)mentioning
confidence: 99%
“…p-Nitrophenyl phosphate has been used as an artificial substrate for Saccharomyces cerevisiae or Schizosaccharomyces pombe FCP1 (14,30). Indeed, p-nitrophenol was generated in proportion to the amounts of FCP1 in the assay (Fig.…”
Section: Ck2 Is the Major Fcp1 Kinase Present In Eggmentioning
confidence: 99%
“…In contrast to the four kinases, there are two known CTD phosphatases in yeast, . Biochemical as well as genetic evidence indicates that both proteins may function as CTD phosphatases in the context of transcription (16,19,20,(25)(26)(27)(28)(29)(30)(31).It is the interplay between these CTD kinases and phosphatases that influences which factors associate with transcribing polymerase and when during the transcription cycle such associations occur. As mentioned, the recruitment of capping enzyme early in the transcription cycle is believed to be one consequence of CTD phosphorylation on Ser5 by Kin28 (6,7).…”
mentioning
confidence: 99%